PENGARUH VARIASI ELEKTRODA DALAM MENURUNKAN KADAR BOD DAN COD LIMBAH CAIR KELAPA SAWIT - Masthura Masthura; Abdul Halim Daulay; Irmawati Koto (UIN Sumatera Utara Medan, 2021)
Research has been carried out which aims to determine the test results of palm oil effluent samples on BOD and COD parameters before and after the electrocoagulation process using Al,Zn, and Fe electrodes. This research uses palm oil effluent from PTPN IV ADOLINA. The results of the BOD test before electrocoagulation were 243 img/l. The results of the BOD test after electrocoagulation with the Al electrode were 100 mg/l, the Zn electrode was i66.8 img/l, and the Fe electrode was 121 mg/l. The test results for COD levels before electrocoagulation were 649 mg/l.The test results for COD levels iafter electrocoagulation with Al electrodes were 350 mg/l, Zn electrodes were 178 mg/l, and Fe electrodes were 315 mg/l. From these electrode variations, ithe best results were obtained for testing the levels of BOD and COD of palm oil liquid waste on the Zn electrode. Key words: Electrode, Electrocoagulation, BOD, COD